Paradygmat antropocentryczny jako kategoria lingwistyczna w badaniu obiektów językowych - Sitarski, Andrzej (Studia Rossica Posnaniensia, 2016)
This study constitutes an attempt to present views from contemporary cognitive linguistics on the definition and realization of the anthropocentric paradigm in the language system. On the basis of reseachers' opinions, the author comes to the conclusion that a language can be analyzed as a peculiar semantic system whose realization is related to a human being. The available results of linguistic object studies, which take into consideration the anthropocentric paradigm, prove that nowadays anthropocentrism should be presented as a linguistic category.